Knowledge, beliefs and attitudes regarding sugar content of process foods - Prada, M.; Garrido, M. V.; Godinho, C. A.; Rodrigues, D.; Lopes, D. (MENU: Journal of Food and Hospitality Research. 3rd Cook and Health Conference, 2019)
The excessive intake of simple sugars, those added to food by producers, cooks or consumers, increase energy in the absence of nutritional value, being associated with multiple health problems (e.g., overweight, periodontal diseases). Recent studies indicate the alarming prevalence of overweight and obesity in Portugal. In addition, more than 95% of the population exceeds the WHO recommended sugar limit (less than 10% of total daily energy intake), stressing the urgent need to address this problem. The results of an online survey conducted in Portugal (n = 1010) examining the eating habits and consumption of foods rich in simple sugars will be presented, namely data on how consumers process different types of nutritional information, their levels of knowledge about WHO recommendations, and the sugar content of processed foods (e.g., categorization of different sugar sources; maximum acceptable threshold levels for sugar). The results are relevant to understand the current problem of excessive intake of free sugars and develop interventions to address it.